The validity of multifrequency bioelectrical impedance measures to detect changes in the hydration status of wrestlers during acute dehydration and rehydration - Utter, A. C.; McAnulty, S. R.; Riha, B. F.; Pratt, B. A.; Grose, J. M. (The Journal of Strength and Conditioning Research, 2012)
The objective of this study was to examine the validity of multifrequency direct segmental bioelectrical impedance analysis (DSM-BIA) measures to detect changes in the hydration status of wrestlers after they underwent 3% acute dehydration and a 2-hour rehydration period. Fifty-six National Collegiate Athletic Association wrestlers: (mean ± SEM); age 19.5 ± 0.2 years, height 1.73 ± 0.01 m, and body mass (BM) 82.5 ± 2.3 kg were tested in euhydrated, dehydrated (-3.5%), and 2-hour rehydration conditions using DSM-BIA to detect the changes in hydration status. The hydration status was quantified by measuring the changes in plasma osmolality (Posm), urine osmolality (Uosm), urine specific gravity (Usg), BM, and weighted segmental impedance at frequencies of 5, 20, 50, 100, and 500 kHz. Weighted segmental impedance significantly increased after a 3.5% reduction in the body weight for all the 5 frequencies evaluated, but it did not return to baseline at 2-hour rehydration. Posm (303 ± 0.6 mOsm/L), Uosm (617 ± 47 mOsm/L), and Usg (1.017 ± 0.001) all significantly increased at postdehydration and returned to baseline at 2-hour rehydration. Estimations of extracellular water were significantly different throughout the trial, but there were no significant changes in the estimations of the total body water or intracellular water. The results of this study demonstrate the potential use of DSM-BIA as a field measure to assess the hydration status of wrestlers for the purpose of minimal weight certification before the competitive season. When employing DSM-BIA to assess the hydration status, the results indicated that the changes in weighted segmental impedance at the frequencies evaluated (5, 20, 50, 100, and 500 kHz) are sensitive to acute changes in dehydration but lag behind changes in the standard physiological (plasma and urinary) markers of hydration status after a 2-hour rehydration period.